Understanding the Role of IL-36 Family Cytokines in Paediatric IBD - Leon, Gemma (Trinity College Dublin. School of Medicine. Discipline of Immunology, 2021)
Despite significant therapeutic advances, the global incidence of Inflammatory Bowel Diseases (IBD) continues to rise, with approximately 25% of these cases reported in childhood and adolescence. Aberrant CD4+ TΗ cell activation and infiltration into the intestines of patients are characteristic of inflammation in IBD and have been demonstrated to occur due to inappropriate innate signalling. In recent times, the innate cytokine family, IL-36, has been implicated in the pathogenesis of IBD, although various studies report pleiotropic roles for these cytokines in the intestines. This study has characterised the effect of IL-36 on the TH cell responses that are associated with the pathology observed in IBD, and confirms a pathogenic role for the cytokine family in the pathogenesis of the disease. We report a prominent role for IL-36 in CD4+ TH cell activation and polarisation, with both in vivo and ex vivo studies demonstrating that IL-36 signalling potently enhances TH1 responses, and synergistically inhibits the generation and suppressive functioning of tolerogenic regulatory T cells (Tregs). In preclinical studies, it appears that IL-36 exploits these effects on CD4+ TH cells to promote the development of T cell mediated colitis, and also enhances the capacity of these pro-inflammatory cells to migrate to the gut, regardless of the tolerogenic influence of retinoic acid. IL-36 can also imprint this proinflammatory gut homing phenotype on human CD4+ TH cells, indicating that the proposed mechanisms of intestinal pathology are functional in humans. Fittingly, we report elevated levels of IL-36α; expression in the colonic tissue and serum of paediatric IBD patients, where the absence of high levels of IL-36 receptor antagonist expression indicates an environment permissive to elevated IL-36 receptor signalling. Furthermore, we identify the presence of the IL-36R on CD3+ T cells in the colon of paediatric IBD patients, demonstrating that the elevated levels of IL-36α; present has the potential to act on these cells. Therefore, IL-36 may be promoting the pathogenesis of the disease in paediatric IBD patients through modulating pathogenic T cell responses. Collectively, these data indicate an important role for IL-36 family members in TH cell-mediated inflammation in the context of IBD, thus rendering these cytokines attractive targets for therapeutic intervention.
APPROVED
Keywords: IBD; T cell; IL-36; Mucosal immunulogy; Immunology; Peadiatric IBD